Nonstandard Forms of Employment in Developing Countries : A Study for a Set of Selected Countries in Latin America and the Caribbean and Europe and Central Asia - Apella, Ignacio (World Bank, Washington, DC, 2018)
The objective of this paper is to study the evolution of the incidence and profile of nonstandard workers in selected countries in Latin America and the Caribbean and Europe and Central Asia in the past two decades. The analysis of the profile of this group of workers focuses on three key characteristics that could approximate their productivity: education level, labor income, and task content (manual/cognitive or routine/nonroutine) performed by the workers in their occupations. While in Latin America most of the countries show a stable prevalence in recent decades, in Europe and Central Asia there is not any common pattern across countries. In contrast, from the point of view of the profile of nonstable employment, there are several common characteristics among these types of workers across countries, such as improved level of education, performance of more intensive nonroutine cognitive tasks, and higher variance of labor income. The findings suggest that nonstandard workers are a heterogeneous group. The increase in the incidence of nonstandard employment and its heterogeneity generates concern about the lower level of insurance against certain risks that workers face. Therefore, a greater understanding of the trends in the prevalence and characteristics of nonstandard workers is needed to design regulation and policies oriented to these types of workers.